Chaotic Biogeography-Based Optimization Approach to Receding Horizon Control for Multiple UAVs Formation Flight. Issue 5 (2015) - Zhu, Weiren; Duan, Haibin
Abstract: In this paper, we proposed a Receding Horizon Control (RHC) scheme which converts multiple Unmanned Aerial Vehicle (UAVs) formation flight problem to a sequence of online optimization problems over a planning horizon. A novel Chaotic Biogeography-Based Optimization (CBBO) approach is presented to find the optimal control inputs for the follower UAVs to maintain coordinated flight with the minimum input cost in each of the planning horizons. Series of simulation results verified the feasibility and effectiveness of our presented approach.